جمع التكسير في القرآن الكريم دراسة صرفية ودلالية - Eltingari, Salih Mahgoub Mohamed (IIUM Press, 2019)
سَعَى هذا البحث من خلال المنهج الوصفيّ إلى دراسة ظاهرة المطابقة في السِّياق القرآني متَّخذاً من صيغ جمع التَّكسير الواردة في الذِّكر الحكيم نموذجاً. وقد بيَّن البحث ما ينشأ من علاقات بين العناصر النَّحويَّة (على مستوى المبتدأ والخبر، والتَّوابع) في واحد أو أكثر من العناصر الآتية: الحالة الإعرابيَّة، أو التَّعيين، أو العدد، أو النوع. وتوصل البحث إلى أنَّ ظاهرة المطابقة جاءتْ وفقاً لما قرَّره النُّحاة، وما خالفهم في بعض الآيات رَدُّوه بحُسْنِ التَّأويل، فجاء مُنسجماً مع قواعدهم، واتفق البحث مع ما ذهب إليه بعض حُذَّاق النُّحاة والمفسرين من صِحَّة بعض الظَّواهر التَّركيبيّة مثل ظاهرة المجاورة مما يُدلل على أنَّ القرآن الكريم نزل وفقاً لكلام العرب، وأشعارهم. ****************************************************** This research sought through the descriptive method to study the phenomenon of conformity in the context of the Holy Quran, based on the forms of broken plurals contained in the Holy Quran. The research has shown the relationship between grammatical elements (based on inchoative and predicate and auxiliaries) in one or more of the following elements: syntax, assignment, numbering or type. The research found that the phenomenon of conformity came according to the decision of the grammarians, and what contradicted their belief in certain verses, was met with good interpretation, and it came in line with their rules, the research agreed with some of the prominent grammarians and commentators on the validity of some synthetic phenomena, such as al-mujawara phenomenon, which indicates that the Holy Quran was revealed according to the words of the Arabs, and their poems.